A novel-charged fibrous media characterized by higher efficiency and lower pressure drop. Issue 12 (2nd December 2019) - Wang, Chih-Te; Lee, Shao-Tai; Li, Li-Yi; Syu, Jin-Yuan; Kuo, Chi-Ching; Lin, Wen-Yinn
Abstract: A new porous fiber shape was produced, one with a longitudinal notch. This new shape increases the surface area and therefore the overall number of pores, which in turn leads to a higher per-fiber surface charge density. Filters with charge generally show advantageous lower pressure drops when compared with the same filtration efficiencies. Although previous studies have hypothesized that increasing the surface area of porous fibers can improve charge capacity, but few experiments have proven this concept. In this study, two different micron-sized fibers were fabricated via electrospinning: smooth ("normal") fibers and the novel notched fibers with surface pores. The fiber profile and voltage drop of the two fibers were measured, and the penetration rate of the two types of fibers before and after charging was measured with aerosol particles ranging from 25 to 478 nm in size. The results showed that the specific surface area of the notched fiber was 47.44 ± 0.67 m 2 g −1, larger than that of the smooth fibers (2.64 ± 0.08 m 2 g −1 ). The notched fiber was charged by negative corona discharge, and the surface capacitance was measured to be −51.2 µC m −2 when the thickness was 0.19 mm, which was also larger than that of the smooth fibers (−38.2 µC m −2 ). When charged, the value of the average quality factor of the notched fibers increased from 0.030 to 0.068 Pa −1 . Overall, the notched fibers demonstrated better filtration efficiency. We concluded that this novel fiber shape delivers both low penetration rates and low pressure drops. Copyright © 2019 American Association for Aerosol Research